Etika baru Imam Al-Ghazali dalam Ihya Ulumuddin dan implikasinya bagi masyarakat modern - Andriansyah, Wiza Atholla; Riyanto, Waryani Fajar (Jurnal Filsafat Indonesia, 2023)
The current social conditions are presented with various kinds of human behavior, good and bad, moral and immoral. This behavior is related to ethics, how humans live life with ethical norms that apply in society or with written norms contained in religious scriptures, both of which aim at the common good. This article aims to explain the behavior of modern society, which has begun to forget the values of goodness even though a Muslim's behavior has been regulated in carrying out social life as it should be included in the current social order. The topic of study in this paper is how the Sufistic ethics of Imam Al-Ghazali in Ihya Ulumuddin and the implications for modern society. The method used in this paper is the analysis of Aristotle's ethical philosophy, by taking an approach to the phenomenon of the social order that is currently developing, and the primary data is the book of Ulumuddin's ihya. The results of this study are that the ethics intended by Imam Al-Ghazali are moral goodness that can nourish individuals in various fields such as politics and socio-economics, welfare, bringing happiness to others and this is in line with the goals of the state, upholding justice, wisdom, and peace and comfort, social services for citizens